Diversidade taxonômica e influência dos fatores ambientais nas comunidades de Collembola (Arthropoda: Hexapoda) da Ilha das Canárias, Maranhão, Brasil - Lima, Maria Geovana de Mesquita (2024)
Collembola are small arthropods, with body lengths ranging from 0.12 to 17 mm, making them barely visible to the naked eye, which contributes to the lack of awareness of this group by a significant portion of the population. This study aimed to provide a faunal survey of the Collembola in the Environmental Protection Area of the Parnaíba Delta – Ilha das Canárias, and to describe how the richness and abundance of their populations are affected by seasonal variations, environmental variables, and spatial characteristics of the region. For specimen sampling, two collections were carried out, one in the rainy season and another in the dry season, with five sampling points containing pitfall traps along a 200 m transect in each phytophysiognomy. Alpha diversity was quantified using species richness and diversity indices (Shannon-Weaver, Simpson, Pielou), while Whittaker's index was used to estimate Beta diversity. Abundance and α diversity were individually assessed in relation to space-time factors through Mixed Generalized Linear Models and Permutational Multivariate Analysis of Variance for β diversity. Non-metric Multidimensional Scaling was used to plot the biotic data matrix in relation to space-time factors. Finally, the abundance of each taxon was related to the sampled environmental variables through Redundancy Analysis. A total of 5,350 specimens were collected, representing three orders, eight families, 23 genera, and 31 morphospecies and one nominal species. The highest abundance during the dry period was observed in the Riparian Forest (1,147), while during the rainy season it was in the Restinga (1,513). Riparian Forest presented the highest α diversity values with higher species richness. β diversity was recorded at higher values in Mangrove. Regarding the influence of environmental variables on species abundance, it was observed that Dicranocentrus sp.1, Proisotoma sp.1, Lepidocyrtus sp.3, and Salina sp.1; were positively influenced by vegetation richness, soil moisture, and litter, while Seira sp.2, Pseudosinella sp.1, and Seira sp.1 were positively associated with soil temperature, air temperature, and pH. The results obtained in this study demonstrate the importance of environmental heterogeneity for the establishment and persistence of Collembola fauna in ecosystems, where greater richness and diversity were observed in more heterogeneous phytophysiognomies. Furthermore, this study represents an initial effort to understand a unique fauna with potentially several new species in a previously unexplored ecosystem.